Effect of Heat Shock Protein A6 on Changes in Meat Quality of Qinchuan Cattle during Postmortem Maturation - MA Xuhua, LI Yalei, LUO Ruiming, ZHANG Xingya (Shipin Kexue, 2023)
In order to investigate the effect of differential expression of heat shock protein family A (Hsp70) member 6 (HSPA6) on the meat quality of Qinchuan cattle during postmortem maturation, the Longissimus dorsi muscle of Qinchuan cattle was stored at 4 ℃ and evaluated for meat quality at 0, 2, 4, 6 and 8 days postmortem. 4D-Label free quantification (4D-LFQ) was used to analyze the expression of HSPA6 and related differential proteins. The results showed that the expression of HSPA6 decreased with increasing storage time, the contents of adenosine triphosphate (ATP), adenosine diphosphate (ADP), adenosine monophosphate (AMP) and reduced form of nicotinamide-adenine dinucleotide (NADH) decreased, the myofibril fragmentation index (MFI) increased, and the shear force and centrifugal loss increased and then decreased. Correlation analysis showed that HSPA6 expression was positively correlated with the contents of ATP and NADH and shear force (P < 0.05) and negatively correlated with MFI and centrifugal loss (P < 0.01), indicating that HSPA6 degradation was closely related to energy metabolism and water retention in beef during storage. Proteomics identified 24 significantly differentially expressed proteins (DEPs) associated with HSPA6 expression, which could cause proteasome-mediated ubiquitin-dependent proteolytic metabolism and cellular proteolysis through carbohydrate derivative binding and purine nucleoside triphosphate binding, in turn causing metabolic disorders or imbalances. These DEPs could also control protein degradation and cell apoptosis, in turn affecting structural changes in muscle and reducing tissue energy levels, and ultimately affecting the tenderness, MFI and water retention of Qinchuan beef through resistance to cellular structural protein degradation.